Claude Parent’s Venise Pavilion (1970): Fonction Oblique’s theorical traces and conceptual legacy - Moreno Moreno, María Pura (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
In the twentieth century's artistic avant-garde, the abstraction contributed to the oblique and asymmetrical vision thanks to a look away from frontalities that would relegate the importance of the binomial space - time. The balance between weight and weightlessness, or statism and instability, led to movements such as Russian constructivism, Neoplasticism, Elementalism or suprematism. Some later spatial utopias, such as that developed by the French group “Architecture Principe”, inherited that theoretical legacy proposing to challenge the spatial order established with its Theory of "Fonction Oblique”, from the cultural context of May 68 French. Its dimensional scope, reflected in its ambitious graphics, ranged from the territorial to the domestic. However, its conceptual foundation was more literally materialized in reduced scale’s experiments, such as the French Pavilion of the 35th Venice Biennale of 1970. This article will identify the theoretical precedents of the sensory experience offered by this ephemeral space, whose main foundation was the questioning of the Cartesian axes of its architectural envelopes -floor, wall and ceiling- and their indiscriminate fusion. The critical analysis of the Pavilion, carried out by Claude Parent integrating architecture and art under the paradigm of the oblique, will allow us to question whether contemporary architectures continue to develop that conceptual legacy, and if at other scales it has ceased to be as utopian as then, and if it makes even more sense.
Keywords: Claude Parent; Venice Pavilion; 1970 Biennial; Fonction Oblique